Designing and Using Public-Private Partnership Units in Infrastructure : Lessons from Case Studies Around the World - Sanghi, Apurva; Sundakov, Alex; Hankinson, Denzel (World Bank, Washington, DC, 2012)
This note contends that public-private partnership (PPP) units for facilitating and managing infrastructure investments have existed for years in many developed countries. Driven in part by growing infrastructure investment, these units have also recently begun to proliferate in the developing world. While governments often seem eager to create such units, not everyone in the global PPP market is convinced of their value. An assessment of eight PPP units around the world examines whether these institutions have contributed to successful public-private partnerships-and if so, under what conditions.